Moderasi Beragama dalam Keberagaman di Masa Covid-19 “Pandangan Pendidikan Hindu” - I Wayan Suasta (UHN I Gusti Bagus Sugriwa Denpasar, 2021)
This article examines religious moderation during the COVID-19 pandemic from the Hindu education perspective. This is intended to get people's activity overview during the COVID-19 pandemic, which is now being carried out through online media. This was done because of the massive amount of information that has occurred through the use of online media since the COVID-19 pandemic hit the world, making people have to be able to sort and choose information fairly and wisely so as not to get trapped in extremism and radicalism with narrow religious understanding. This research is a type of library research, where the data comes from literature related to the research object which is analyzed and presented in descriptive qualitative form. From the JAPAM (Jurnal Pendidikan Agama) Vol. 1, No. 2 | 85 analysis results, it is confirmed that the Hindu education view, can be used as the basis for sorting, selecting and utilizing information fairly and wisely. So that an understanding or attitude is formed that respects all religious traditions as truth. On that basis, actually, peace and harmony can be realized in the real practice of religious behaviour, with the awareness that all human beings are essentially composed of holy souls. Everyone has the right to live on earth according to their respective beliefs and faith. This earth is the home of all living things. So with the mantra Om swastiastu, Om anubadrah kertvu yantu visvatah, Om semesta loka sukinoh bhavantu, Om santih, santih, santih, Om, can be used as basic principles to interpret religious moderation in diversity on the Covid-19 era from Hindu education perepectives.